Neuropsychological features of patients of reproductive age diagnosed with breast cancer at the stage of surgical treatment using xenon-oxygen therapy - D. A. Rozenko; A. I. Shikhlyarova; L. N. Vaschenko; N. N. Popova; Yu. Yu. Arapova; A. Yu. Ardzha; A. A. Korobov (Исследования и практика в медицине, 2021)
Purpose of the study. To study functional changes in the neuropsychological status of reproductive age patients with newly diagnosed breast cancer and to assess the possibility of using xenon-oxygen therapy to correct disorders.Patients and methods. This study included 60 reproductive age patients with newly diagnosed breast cancer who were undergoing surgical treatment at the Department of Bone, Skin, Soft Tissue and Breast Tumors of the National Medical Research Centre for Oncology of the Ministry of Health of Russia from 2018 to 2020. The main group included 30 patients with breast cancer diagnosed at the surgical stage of combined treatment, who underwent a rehabilitation course of xenon-oxygen therapy in the early postoperative period. The control group was formed from patients with the same diagnosis, without the use of this therapy. The functional state of the central nervous system in all patients was assessed by the parameters of the electroencephalography (EEG) bioelectrical activity. For the final assessment of the physiological and psychological state of the patients, a standardized questionnaires of the quality of life – ESAS, MOS-SF‑36, were used. Statistical data processing was performed using the Statistica 10 software package. Results. During the study, statistically significant differences were found in the assessment of subjective indicators, so in the group of patients using xenon-oxygen therapy, there was an improvement in well-being by 2.6 times, a decrease in depression by 2.3 times, a decrease in symptoms of nausea by 3 times, anxiety 1.9 times (p < 0.05). Against the background of an improvement in the psychophysiological state, the EEG showed a significant increase in the power of slow delta and theta rhythms, an increase in the power of the alpha rhythm and a decrease in the power of the beta rhythm, while in the patients of the control group only a decrease in the power of the beta rhythm was noted.Conclusion. The early postoperative period in patients with newly diagnosed breast cancer is characterized by the formation of a depressive symptom complex. The use of a course of xenon-oxygen therapy contributes to the normalization of the subjective feeling of physical and psychological health, increasing vital and social activity. Changes in the indicators of brain bioelectric activity and an improvement in psychophysiological state occur against the background of changes in brain activity caused by the normalizing effect of xenon.